ANALISIS PENGENDALIAN INTERN ATAS PIUTANG DAGANG PADA PT. SURYA MITRA SENTOSA PONTIANAK - Fara Dina (Jurnal Khatulistiwa Informatika, 2016)
In this research, the writer used case study method with PT. Surya Mitra Sentosa Pontianak, as the research object, with the direct involvement of the writer into the field to gain the data in order to study the company’s condition based on fact. To analyze the data, the writer rised organization structure, sales flowchart and elimination of receivables and internal control questionnaire. Base on the result of internal control questionnaire, at can be concluded that internal control over receivables and credit sales in PT. Surya Mitra Sentosa is necessarily effective.